2011
DOI: 10.1143/jjap.50.085701
|View full text |Cite
|
Sign up to set email alerts
|

Schottky-Barrier-Induced AC Surface Photovoltages in Au-Precipitated n-Type Si(001) Surfaces

Abstract: We have studied the behavior of Au clusters on the top surface of a SiO2 film and/or at the SiO2/Si interface as a function of oxidation temperature between room temperature (RT) and 500 °C in conjunction with a Schottky-barrier-induced AC surface photovoltage (SPV) and an enhanced SiO2 growth due to Au at 500 °C. Upon rinsing an n-type Si(001) wafer in a Au-contaminated aqueous solution, precipitated Au atoms are observed as clusterlike Au granules on the top surface of SiO2 (Au surface concentration, 2.3 ×10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
1

Year Published

2011
2011
2013
2013

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 20 publications
0
9
1
Order By: Relevance
“…The AFM image showed a smooth and flat surface in contrast to the clusterlike Au granules observed in the Au-aqueous-solution-rinsed Si surface. 23) This indicates that the Cr atom layer can cover the bare Si surface. This result will be discussed in x3.4.…”
Section: Afm Image Of Cr-aqueous-solution-rinsed P-typementioning
confidence: 96%
See 1 more Smart Citation
“…The AFM image showed a smooth and flat surface in contrast to the clusterlike Au granules observed in the Au-aqueous-solution-rinsed Si surface. 23) This indicates that the Cr atom layer can cover the bare Si surface. This result will be discussed in x3.4.…”
Section: Afm Image Of Cr-aqueous-solution-rinsed P-typementioning
confidence: 96%
“…On the other hand, in the n-type Si(001) surface dipped in hydrofluoric acid (HF) aqueous solution (hydrophobic in surface) and rinsed with Au aqueous solution, clusterlike Au granules are observed on the Si hydrophobic surface by atomic force microscopy (AFM), resulting in the formation of Schottky barrier contact. 23) Cr-deposited surfaces have not been investigated yet by AFM. In principle, a Cr layer deposited on a p-type Si surface is not expected to generate a Schottky barrier in contrast to that deposited on an n-type Si surface.…”
Section: Introductionmentioning
confidence: 99%
“…10,11) It was observed that when n-type Si(001) wafers with a hydrophobic surface are rinsed in Au aqueous solution, an alternating current (AC) surface photovoltage (SPV) [12][13][14][15][16] is generated by the deposition of Au on the Si surface (Au/n-Si Schottky barrier), demonstrating that depleted or weakly inverted layers can be formed at the Au/n-Si interface. 17) It was postulated that this AC SPV is caused by the Schottky barrier. 17) The occurrence of AC SPV differs fundamentally from that originally described as a metal-induced negative oxide charge (Q mi ) 18) shown by (AlOSi) À networks and/or AlO 2 À in n-type Si.…”
Section: Introductionmentioning
confidence: 99%
“…17) It was postulated that this AC SPV is caused by the Schottky barrier. 17) The occurrence of AC SPV differs fundamentally from that originally described as a metal-induced negative oxide charge (Q mi ) 18) shown by (AlOSi) À networks and/or AlO 2 À in n-type Si. 19) Thus, the Au/n-Si interface should be investigated with reference to the Schottky barrier in detail.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation